Population structure of two bamboo species in relation to topographical units in the Republic of Benin (West Africa): implications for sustainable management. - Tovissodé, Frédéric Chenangnon; Honfo, Hermann; SALAKO, Kolawolé Valère; GNANGLE, Césaire; Mensah, Sylvanus; Glèlè Kakaï, Romain Lucas (My University, 2015)
A study was carried out in two phytodistricts (Ouémé-valley and Plateau) to assess the population structure of two bamboo species (Oxytenanthera abyssinica (A. Rich.) Munro and Bambusa vulgaris Schrad. ex J.C. Wendl. in two topographical units: plateau and wetlands. In each phytodistrict, bamboo stands were randomly selected in each topographical unit for inventory using a 0.25-ha square plot. Structural parameters of bamboos were computed and compared using a Wilcoxon rank test. Spatial distribution of the two bamboos was also assessed using the method of neighbourhood density in relation to a focal point. The observed culm diameter distribution was established for each stand and adjusted to the two-parameter Weibull distribution. Oxytenanthera abyssinica showed the highest culm and clump density values in both wetlands and plateau whereas B. vulgaris showed greater values of mean diameter and dominant height whatever the habitat. Diameter structures of bamboo stands showed a right asymmetric distribution and bamboo spatial distribution was highly aggregative, especially in wetlands. No significant difference in mean relative neighbourhood density between species was noted. However, a significant difference was observed between wetlands and plateau (p < 0.001) indicating strong influence of the topographical units on the relative neighbourhood density of bamboo species. All of these findings are determinants in designing suitable management strategies for bamboo populations in Benin, particularly with the increasing demand to build fish-traps and shelter in the traditional fishing systems “Acadja”.
Keywords: bamboo populations; structure; spatial patterns; Benin; West Africa